Impact Of Fly Ash (Flyash) Fineness On Stability and Density Of Asphalt- Concerete (AC-WC) - Rosyad F (International Conference on Engineering and Technology Development (ICETD), 2017)
In this study, the use of materials of stone dust (fly ash) as material substitution fine fraction on asphalt Concrete mix AC-WC to study the properties and Durabilitasnya.Beton Marshall asphalt is one type of flexible pavement pavement construction. This research focuses on the extent to which the influence of fineness Abu fly to Mix Concrete Asphalt -WC tehadap stability and density of the asphalt concrete mixture. and in the end it is hoped will fly coal ash that was once a waste material can be used as a substitution material fine fraction and alternative filler in road construction penilitan raya.kesimpulan obtained from analysis of the influence of the fineness of the stability and density of asphalt concrete campuaran AC-Wc are as follows stability: Value stability of the mixture in the review of fineness variation tends to increase from variations in levels of fly ash substitution occurs at the rate of 6% optimum zone 3 is equal to 1.435kg and at the level of 8% zone 3 decreased to 1.421kg.DensityValues Density (Bulk Density Standard) mix in the review of fineness variation tends to increase. variations in levels of fly ash substitution occurs at the rate of 8% optimum zone 3 is equal to 2,421kg / cc. Some Suggestions can be submitted to refine the results Research the performance of asphalt concrete (AC-WC) by using substitution fineness and content of fly ash that is: a). For further research in order to analyze the use of the optimum bitumen content of the usage levels of substitution optimum fly ash because of the greater use of ash Marshall then fly parameter values tend to be less than optimal. B) It is advisable to combine other types of materials substitution with fly ash material to obtain results that are more economical